2020
DOI: 10.1002/jeq2.20000
|View full text |Cite
|
Sign up to set email alerts
|

Nitrate availability affects denitrification in Phragmites australis sediments

Abstract: Understanding relationships between an increase in nitrate (NO3−) loading and the corresponding effects of wetland vegetation on denitrification is essential to designing, restoring, and managing wetlands and canals to maximize their effectiveness as buffers against eutrophication. Although Phragmites australis (Cav.) Trin. ex Steud. is frequently used to remediate nitrogen (N) pollution, no information is available on how NO3− concentration may affect plant‐mediated denitrification. In the present study, deni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 79 publications
(147 reference statements)
0
8
0
Order By: Relevance
“…In addition, TN and TP were also reported as determinants for the growth and community succession of P . australis (González‐Alcaraz et al, 2012; Soana, Gavioli, Vincenzi, Fano, & Castaldelli, 2020) but failed to show significant impacts here. Further analysis showed that TN ranged from 0.11 to 0.26 g kg −1 , and TP ranged from 0.41 to 0.70 g kg −1 in the experimental area.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…In addition, TN and TP were also reported as determinants for the growth and community succession of P . australis (González‐Alcaraz et al, 2012; Soana, Gavioli, Vincenzi, Fano, & Castaldelli, 2020) but failed to show significant impacts here. Further analysis showed that TN ranged from 0.11 to 0.26 g kg −1 , and TP ranged from 0.41 to 0.70 g kg −1 in the experimental area.…”
Section: Discussionmentioning
confidence: 64%
“…For the spatial structures shown in Figure 7b, the first two and three dimensions accounted for 36.87 and 43.76% of the explainable variance, respectively, and only SWC was correlated to the plant traits' matrix at a 95% confidence level (p = 0.032). In addition, TN and TP were also reported as determinants for the growth and community succession of P. australis (Gonz alez- Alcaraz et al, 2012;Soana, Gavioli, Vincenzi, Fano, & Castaldelli, 2020) but failed to show significant impacts here. Further analysis showed that TN ranged from 0.11 to 0.26 g kg À1 , and TP ranged from 0.41 to 0.70 g kg À1 in the experimental area.…”
Section: Influence Of Environment Factors On Plantsmentioning
confidence: 63%
“…For the spatial structures shown in Figure 7B, the first two and three dimensions accounted for 36.87 % and 43.76 % of the explainable variance, respectively, and only SWC was correlated to the plant traits' matrix at a 95 % confidence level (P = 0.032 ). In addition, TN and TP were also reported as determinants for the growth and community succession of P. australis (Gonzalez-Alcaraz et al, 2012;Soana et al, 2020) but failed to show significant impacts here. Further analysis showed that TN ranged from 0.11 g/kg to 0.26 g/kg, and TP ranged from 0.41 g/kg to 0.70 g/kg in the experimental area.…”
Section: Influence Of Environment Factors On Plantsmentioning
confidence: 60%
“…On the other hand, the analysis of water chemistry did not highlight any nutrient retention process due to P. australis presence. Even though phytodepuration function of common reed beds are widely documented [65], denitrification processes are not supported in absence of constant water fluxes [66], such as the case of Valle Santa wetland. The high concentration of NO 3 − is coherent with the diffuse agricultural pollution that occur in the surrounding land and within the basin of Idice stream.…”
Section: Discussionmentioning
confidence: 99%